Electrochemical Reconstruction Engineering: Metal–Organic Gels as Pre‐Catalysts for NiOOH/FeOOH Heterostructure to Boost Oxygen Evolution Reaction - Jia-Yang Luo; Yi Yuan; Heng-Yu Ruan; Xue-Qian Wu; Ya-Pan Wu; Shuang Li; Gaixia Zhang; Shuhui Sun; Dong-Sheng Li (Small Structures, 2023)
Metal–organic gels (MOG) as new types of soft materials have shown promising applications in various fields such as chemosensors, environmental remediation, and gas adsorption/separation, owing to their high porosity, low density, and high surface area. However, the application of MOG materials in energy electrocatalysis and the active components made from them are rarely perceived. Herein, a new electrochemistry‐driven reconstruction strategy to synthesize the NiOOH/FeOOH heterostructure from MOG materials is reported. The reconstructed NiOOH/FeOOH exhibits superior oxygen evolution reaction activity and excellent stability, owing to the synergistic effect of bimetallic centers, the abundant interface between NiOOH and FeOOH, and the plentiful defects. Impressively, the activated Re–FeNi–MOG‐4 electrocatalyst displays remarkable catalytic activity with a low overpotential of 220 mV at a current density of 10 mA cm−2 and a small Tafel slope of 48 mV dec−1 in alkaline electrolyte, outperforming most recently reported electrocatalysts. Herein, a facile and effective electrochemical reconstruction engineering of pre‐catalysts is provided and the evolution of self‐reconstruction of MOG materials for accelerating the kinetics of the electrocatalytic process is highlighted.